2014
DOI: 10.1038/nn.3725
|View full text |Cite
|
Sign up to set email alerts
|

Leptin signaling in astrocytes regulates hypothalamic neuronal circuits and feeding

Abstract: We have shown that synaptic re-organization of hypothalamic feeding circuits in response to metabolic shifts involves astrocytes, cells that can directly respond to the metabolic hormone, leptin, in vitro. It is not known whether the role of glia cells in hypothalamic synaptic adaptions is active or passive. Here we show that leptin receptors are expressed in hypothalamic astrocytes and that conditional, adult deletion of leptin receptors in astrocytes leads to altered glial morphology, decreased glial coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
275
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(301 citation statements)
references
References 28 publications
15
275
2
Order By: Relevance
“…Third, given that LDHA is selectively expressed in the astrocytes (21)(22)(23)(24) and that leptin enhances LDHA-dependent glucose sensing in the hypothalamus as currently described, leptin signaling and glucose-lactate metabolism could intersect within the astrocytes to improve whole-body metabolic control. This postulation is collaborative with findings indicating that leptin signaling in the astrocytes regulates feeding (27) and that insulin signaling in the astrocytes enhances central glucose sensing (28). In summary, we here report, for the first time to our knowledge, that leptin enhances LDHA-dependent hypothalamic glucose sensing to regulate glucose production in high-fat fed in vivo conditions.…”
Section: Discussionsupporting
confidence: 87%
“…Third, given that LDHA is selectively expressed in the astrocytes (21)(22)(23)(24) and that leptin enhances LDHA-dependent glucose sensing in the hypothalamus as currently described, leptin signaling and glucose-lactate metabolism could intersect within the astrocytes to improve whole-body metabolic control. This postulation is collaborative with findings indicating that leptin signaling in the astrocytes regulates feeding (27) and that insulin signaling in the astrocytes enhances central glucose sensing (28). In summary, we here report, for the first time to our knowledge, that leptin enhances LDHA-dependent hypothalamic glucose sensing to regulate glucose production in high-fat fed in vivo conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The physiological relevance of the astrocyte plasticity identifi ed here is not well understood, but the authors suggest that it might contribute to the maturation of efficient synaptic strength during the postnatal development of the brain and basic cognitive functions in the adult brain by controlling the access of astrocytic processes to synaptic glutamate. It is noteworthy that similar changes in the glial coverage of synapses were previously observed in the hypothalamus, contributing to the regulation of several key processes such as lactation [9] , osmoregulation [10] , reproductive function [11] and more recently, feeding behavior [12] . Since astroglial …”
supporting
confidence: 59%
“…Noteworthy, the neural circuit for feeding regulation is not limited to neural cells. For instance, the glial cells in the brain were proved to be involved in the regulation of feeding [6,7,8]. Yang et al [9] recently found that stimulation of medial hypothalamic astrocytes could directly reduce the basal- and ghrelin-evoked feeding behavior through inactivation of AgRP/NPY neurons in the ARC.…”
Section: Introductionmentioning
confidence: 99%